Clinical Outcomes and Economic Impact of Oritavancin for Gram-Positive Infections: A Single Academic Medical Center Health System Experience - Lauren E. Brownell; Meagan L. Adamsick; Erin K. McCreary; Joshua P. Vanderloo; Erika J. Ernst; Emily R. Jackson; Lucas T Schulz (Adis, Springer Healthcare, 2020)
Abstract Background Vancomycin treatment of complicated Gram-positive infections is associated with laboratory monitoring, nephrotoxicity, and multiple daily dosing. Oritavancin, a lipoglycopeptide antibiotic with a once-weekly dosing strategy and similar but slightly broader spectrum of activity, presents several opportunities over vancomycin to improve compliance and convenience for the patient. Minimal real-world clinical and acquisition cost data in the inpatient setting and clinical data surrounding multiple dosing in the outpatient setting have limited oritavancin use despite its potential logistic advantages. Objectives We describe inpatient and outpatient oritavancin administration, clinical outcomes, and economic impact. Methods This was a single-center, retrospective case series of patients treated with at least one dose of oritavancin between May 2015 and September 2017 at an academic medical center in the USA. A simplified cost-avoidance analysis was conducted assuming the patient had a national health insurance plan and focused on hospital days prevented. Results Seventy-five patients received oritavancin during the study period. The most common use of oritavancin was in patients with acute bacterial skin and skin structure infections (ABSSSI), defined as cellulitis, abscess or non-surgical wounds (n = 25, 33%), followed by surgical wound infections (n = 12, 16%) and osteomyelitis or septic arthritis (n = 10, 13%). Clinical cure or improvement was achieved in 68 patients (93.2%), while five patients (6.8%) failed treatment; adverse reactions were reported in nine patients (12%). Thirty-five patients received oritavancin as inpatients; 20 patients (57%) had at least one hospital day avoided due to inpatient oritavancin administration resulting in a total cost avoidance of US$343,654. Conclusion In this series of 75 patients with Gram-positive infections, oritavancin treatment resulted in clinical cure or improvement in most patients, and was generally well tolerated. Inpatient administration may avoid costs and outpatient administration is a reasonable consideration for patients in which prolonged antibiotic therapy is necessary.